2015
DOI: 10.1074/jbc.m115.656496
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in Isoform 3 of the Plasma Membrane Ca2+ Pump Impairs Cellular Ca2+ Homeostasis in a Patient with Cerebellar Ataxia and Laminin Subunit 1α Mutations

Abstract: Background: Mutations in plasma membrane Ca 2ϩ -ATPase (PMCA) isoform 3 and in laminin subunit 1␣ have previously been linked to ataxic phenotypes. Results: A novel PMCA3 missense mutation co-occurring with a compound heterozygous mutation in laminin subunit 1␣ impaired cellular Ca 2ϩ homeostasis. Conclusion:The two mutations could work synergistically to generate the disease phenotype. Significance: A digenic mechanism could be responsible for this case of cerebellar ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Mutations in several genes with known functions related to calcium homeostasis cause monogenetic forms of ataxia, including those encoding the P type voltage-gated Ca 2+ channel (Zhuchenko et al, 1997), mGluR1 (Guergueltcheva et al, 2012), the type 1 IP 3 R (van de Leemput et al, 2007), the type 3 Ca 2+ ATPase (Zanni et al, 2012; Calì et al, 2015), and possibly TRPC3 (Fogel et al, 2015). Moreover, cerebellar PNs abundantly express many genes involved in calcium homeostasis and a large fraction of these genes are transcriptionally dysregulated in various SCAs (Serra et al, 2004; Schorge et al, 2010; Bettencourt et al, 2014; Ingram et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in several genes with known functions related to calcium homeostasis cause monogenetic forms of ataxia, including those encoding the P type voltage-gated Ca 2+ channel (Zhuchenko et al, 1997), mGluR1 (Guergueltcheva et al, 2012), the type 1 IP 3 R (van de Leemput et al, 2007), the type 3 Ca 2+ ATPase (Zanni et al, 2012; Calì et al, 2015), and possibly TRPC3 (Fogel et al, 2015). Moreover, cerebellar PNs abundantly express many genes involved in calcium homeostasis and a large fraction of these genes are transcriptionally dysregulated in various SCAs (Serra et al, 2004; Schorge et al, 2010; Bettencourt et al, 2014; Ingram et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of a single copy of the gene encoding the plasma membrane calcium pump PMCA also results in ataxia in mice (Empson et al 2010), and rare mutations in this gene have been found in human ataxia patients (Zanni et al 2012;Cali et al 2015). Taken together, such findings strongly suggest that elevated calcium levels, one of the possible outcomes of increased activity in the mGluR signalling cascade, can compromise the health of PNs and lead to ataxia.…”
Section: Evidence Suggesting That Increased Mglur Signalling Plays a mentioning
confidence: 95%
“…; Cali et al . ). Taken together, such findings strongly suggest that elevated calcium levels, one of the possible outcomes of increased activity in the mGluR signalling cascade, can compromise the health of PNs and lead to ataxia.…”
Section: Introductionmentioning
confidence: 97%
“…The cytoplasmic domains contain an actuator domain A, a phosphorylation domain P and a nucleotide binding domain N. The loop between TM4 and TM5 contains the phosphorylation and ATP binding sites. There are two calcium ion binding sites (Baig et al 2011, Cali et al 2015. Deletion mutations of ATP2B3 were reported together with ATP1A1 (Beuschlein et al 2013) at p.L425_ V426del and p.V426_V427del, which are located in TM4 (Fig.…”
Section: Atp2b3mentioning
confidence: 99%